Pengaruh Memorable Tourist Experience (MTE) terhadap Affective Commitment dan Behaviors Storytelling - Eny Endah Pujiastuti; Aninda Maharaniputri; Adi Soeprapto (Journal of Tourism and Creativity, 2021)
Affective Commitment is understood as the main key construct in relationship marketing research. Its explains how individual emotionally attached to their partner in consumption relationship. Affective Commitments can encourage tourists to tell others so that a strong relationship can be established between tourists and destinations. The aim of this study are to analyze and prove: (1) the effect of memorable tourist experience (MTE) on affective commitment, (2) the effect of affective commitment on storytelling behavior, (3) memorable tourist experience (MTE) on behavior storytelling. Research Location at Borobudur Temple. Tourists who have visited the Borobudur Temple as a research sample. The data collected was 130 questionnaires, processed using AMOS SEM. The conclusion from this study shows that (1) memorable tourist experience (MTE) significantly influences affective commitment, (2) affective commitment significantly influences storytelling behavior, (3) memorable tourist experience (MTE) significantly influences behavior storytelling. The implication of the research findings is that the manager must provide a memorable experience to tourists so that if the tourists feel pleasure, this will in turn lead to affective commitment and will tell others. Research limitations such as the closure of the Borobudur Temple caused by the Covid 19 pandemic, so the sample used is tourists who have visited the Borobudur Temple before the Covid 19. pandemic. Suggestions for further research, the researcher recommends using a sample of tourists who have visited the destination with the close distance between the visit to the destination and the time of data collection. Researchers can also add other variables to study the impact of Memorable Tourist Experience (MTE) on destinations and tourists.